Keselarasan Tema pada Cerita Berjudul Cut Vi dan Sebab Aku Cinta, Sebab Aku Angin dalam Kumpulan Cerpen Juragan Haji Karya Helvy Tiana Rosa: Thematic Alignment in Short Stories Titled Cut Vi and Sebab Aku Cinta, Sebab Aku Angin in Helvy Tiana Rosa’s “Anthology Juragan Haji” - Kumalasari, Yasinta (Journal of Literature and Education, 2025)
This study aims to identify the themes and thematic alignment in the short stories Cut Vi and Sebab Aku Cinta, Sebab Aku Angin from Helvy Tiana Rosa's anthology Juragan Haji. This research employs a qualitative approach, aiming to describe and interpret the collected data. The data consist of quoted dialogues, sentences, and paragraphs. These data were gathered using reading and note-taking methods. The findings of this study reveal both major and minor themes, as well as a thematic alignment between the two stories. The aligned major themes are tragedy and humanitarian action, while the aligned minor themes are the love and spirituality of the characters within the stories.